Growth Hacking Capability of SMEs: The Roles of Digital Mindset, Collaborative Capability, and Organizational Agility - Fansuri Munawar; Rini Handayani (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study examines the Growth Hacking Capability (GHC) of creative industry Small and Medium-sized Enterprises (SMEs) in West Java, Indonesia. Drawing on Dynamic Capability Theory, this study conceptualizes GHC as an organizational capability that enables SMEs to learn from customer data, pilot small experiments, and adapt product features based on feedback. This study is novel because it combines a digital mindset, collaboration, and agility as antecedents of GHC, representing cognitive, relational, and adaptive capability foundations. Research Methodology: We surveyed 150 creative industry SME owners and managers in West Java and analyzed the data with Partial Least Squares Structural Equation Modeling (PLS SEM) SmartPLS 4.0. Results: A digital mindset, collaborative capability, and organizational agility positively affect GHC, which in turn boosts market responsiveness and innovation performance. GHC increases firms' speed in responding to customer needs, leading to more rapid product updates and higher innovation performance. Therefore, market responsiveness links GHC to innovation. Conclusions: GHC is not merely a digital marketing practice but an organizational capability that enables SMEs to transform digital learning, collaboration, and agility into responsiveness and innovation. Limitations: This study is limited to creative-industry SMEs in West Java and explains GHC, market responsiveness, and innovation performance through selected internal capabilities. Future studies may include additional variables, such as entrepreneurial orientation, absorptive capacity, digital marketing capability, financial resources, leadership support, market dynamism, firm size, and firm age. Contributions: This study advances Dynamic Capability Theory by explaining how cognitive, relational, and adaptive capability foundations jointly shape GHC in resource-constrained SMEs. It also enriches the GHC literature by showing how GHC is developed and translated into innovative outcomes through market responsiveness.